PENGARUH TINGKAT INTENSITAS PEMBERIAN LATIHAN SOAL TERHADAP PRESTASI BELAJAR SISWA DALAM MATA PELAJARAN PKn - novita barla; Adelina Hasyim; M. Mona Adha (FKIP Unila, 2012)
Exercise is an activity of repetition in the learning process that aims to motivate students to better understand the learning materials in order to obtain better results. With the provision of the exercises that the students are expected to help improve student learning outcomes especially in subjects Citizenship Education. The purpose of this study was to clarify the effect of the intensity level of giving exercises on student achievement in the subjects of Civics class VII at Junior High School 21 Bandar Lampung academic year 2012/2013. The research method used in this study is a quantitative method of testing the influence. The samples in this study were 30. Data analysis using Chi Square. The results showed that: (1) the influence of the intensity of the exercises provision (X) dominant in the category of influential with percentage 36.6%, (2) achievement (Y) dominant in the high category with the percentage of 40%, (3) the results of research shows there is a positive relationship, significant, and category tinngi closeness between the effect of the intensity level of the provision of the learning exercises, which means that the prominence of the level of intensity of exercises possible giving further improve student achievement in the subjects of Civics.Keywords: Exercise, Achievement, Citizenship Education